Technological potential of Hevea brasiliensis clones for energy uses and furniture - Amorim, Erick Phelipe (Universidade Federal de São Carlos, 2020)
Hevea brasiliensis is an important Brazilian forest species, as its main product is latex, responsible for originating various synthetic products for different uses. The state of São Paulo is the leader of plantations of species, representing 56% of planted areas, this leadership is due to research by IAC-Instituto Agronômico de Campinas, which has been seeking to develop clones with dual aptitude for latex and wood production. The latex extraction cycle from a rubber plantation varies from 25 to 30 years, after this period there is replanting, and wood is destined for lower added value uses, generally domestic uses, with few studies addressing its technological characteristics. Based on the above, the objectives of work were to characterize technological properties of 10 clones of 12-year-old: IAC 40, IAC 41, 64B 850, IAC 311, IAC 301, IAN 873, GT1, PB 330 and FX 2261 clones for potential energy uses, furniture production, characterization of anatomical arrangement and basic density from pith-bark. The work was divided into four chapters. The first provides a general introduction to aspects of the species. The second chapter characterizes wood for energy use through chemical, energetic characteristics, basic wood density, fiber dimensions, thermogravimetric profile (TGA) and spectroscopy Infrared (FTIR). The third chapter addresses physical properties as to basic density, volumetric shrinkage and mechanical properties as to compression parallel to the grain, static flexion being obtained elasticity and rupture modules and wood machining aiming furniture production. The fourth chapter characterizes anatomy and basic density of wood from pith to thebark, since there are few studies that report these properties of clones cultivated in Brazil. The results show that clones present satisfactory characteristics for bioenergetic uses, being observed superior characteristics for clone IAC 311, being similar to other clones. However, clones IAC 301 and FX 2261, presented characteristics inferior to the others for this purpose of use. In the study of physical and mechanical properties, clones are classified as having low density, medium dimensional stability and satisfactory values of modulus of elasticity and rupture. In the analysis of surface through machining tests, wood is classified as good to excellent, presenting light grain lift, low percentage of cracking and light grain chilling on the surface. Superior physical and mechanical characteristics were observed for clones 64B 850 and GT1. However, the other clones have similar characteristics and can be used to furniture production and reduce the exploitation of native forests for this purpose and adding value to wood. In the study of the radial variation of anatomical features and basic density, distinct anatomical arrangements were observed between clones. Most of clones are radially characterized by increasing fiber length and decreasing fiber wall thickness, increasing vessel diameter and decreasing vessel frequency. The dimensions and frequency of rays showed different behaviors, however, for most clones, there is an increase in height and width and a decrease in frequency. The basic density presents different patterns between clones, higher densities in the middle positions was observed for most of clones.
Potencial tecnológico de clones de Hevea brasiliensis para usos energéticos e móveis
Keywords: Wood quality; Technological characterization; Wood properties; Qualidade da madeira; Caracterização tecnológica; Propriedades da madeira; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL